PENGEMBANGAN POLA KEMITRAAN DALAM RANGKA PENGENTASAN KEMISKINAN DI JAWA TIMUR - Siswoyo Hari Santosa; Dewi Prihatini; Agung Purwanto; Aisah Jumiati; Djoko Susilo (UNEJ e-Proceeding)
To develop and strengthen the small business sector, one important strategy is partnering with medium and large business sector through a partnership that is based on the principle of mutual need, mutually reinforcing and mutually beneficial. In general, this study aimed to analyze the effectiveness of a partnership for the empowerment of the poor in East Java. Based on the research, programs and activities that have been implemented are as follows: (a) Program for Community Empowerment; (B) Development Program Rural Economic Institute; (C) Community Participation Program In Village Building; and (d) Capacity Building Program Apparatus village government; Based on these results is the recommended that the partnership model from the perspective of the system at least, there are 3 types suitable to be applied in the community empowerment program in East Java province, namely: Vertical Linkage Backward, Forward Vertical and Horizontal Linkage Linkage.